Homeland : Season 2 - Cuesta, Michael, 1963-; Kerrigan, Lodge; Danes, Claire, 1979-; Lewis, Damian, 1971-; Baccarin, Morena (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2013)
When a rescued POW returns home after eight years, a CIA agent begins to believe that the war hero may be a danger to America.
The smile -- Beirut is back -- State of independence -- New car smell -- Q&A -- A Gettysburg address -- The clearing -- I'll fly away -- Two hats -- Broken hearts -- In memoriam -- The choice.
Dolby digital 5.1, wide screen 1.78:1.
Features: deleted scenes, Return to the Homeland : filming in Israel, The border, Damian Lewis : a personal video diary, The choice : the making of the season finale.
Claire Danes, Damian Lewis, Morena Baccarin, David Harewood, Diego Klattenhoff.
Originally broadcast on television in 2012.
TV rating: Not rated.
In English with optional French or Spanish subtitles.
Keywords: United States. -- Central Intelligence Agency -- Drama; Prisoners of war -- Drama; Soldiers -- United States -- Drama; Terrorism -- Drama; Thrillers (Television programs); Detective and mystery television programs; Television series; Fiction television programs; Video recordings for the hearing impaired; Detective television programs; Mystery television programs